GAP ANALYSIS OF THE NAHWU LEARNING PROGRAM USING MALCOLM PROVUS'S DISCREPANCY EVALUATION MODEL AT MADRASAH ALIYAH AR-RISALAH PADANG - Habib, Ikhwanul; Hasanah, Mamluatul; Basid, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to identify the standards, performance, and discrepancies in the process of teaching nahwu at MA Ar-Risalah Padang based on Malcolm Provus’ Discrepancy Evaluation Model. This research employs a qualitative design with a case study approach. Data were collected through semi-structured interviews with the vice principal for the Middle Eastern division, subject teachers, and students. In addition, participatory observation was conducted during the learning process, and supporting documents were collected. Data analysis followed the model of Miles and Huberman, while data validity was ensured through triangulation techniques. The findings reveal that MA Ar-Risalah Padang exhibits several discrepancies, particularly in the dimension of teaching methods, which are still dominated by teacher-centered approaches through lectures. There is also limited student participation in the learning process, the four language skills are not consistently emphasized, and the implementation of communicative and deep learning approaches has not been optimal. The implications of this study suggest that, based on Malcolm Provus’ evaluation model, continuous evaluation is necessary to minimize the gap between standards and instructional practices. Teachers are encouraged to adopt more varied methods and media and to move away from lecture-based instruction. Furthermore, the institution should provide specialized training for Arabic language teachers.